THE EFFECTIVENEES OF INFORMATION PROCESSING TEACHING MODEL OF THE INDUCTIVE AND CONCEPT ATTAINMENT IN TEACHING ESP AT UNIVERSITAS BUMIGORA - Hilda Hastuti; Erwin Suhendra (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2021)
This research has five goals. If there is an effectiveness among IT, CA, and conventional models; the second is if the IT the model is more effective than the conventional one; the third is if the CA model is more effective than the conventional one; the fourth is if the IT model is more effective than the CA model; and the fifth is if the IT model is the most effective among the three models in the teaching ESP at Universitas Bumigora. This research is quasi-experimental with a randomized pretest-posttest control group design. The population is all of the students of ESP at Universitas Bumigora. The sample used the simple cluster random sampling technique. The instruments used are assessment rubric and English assignment sheet. The data is collected through the assignment of English and assed with English assessment rubric. The data analyzed using two-way ANOVA. The result of this study shown that there is significance difference among three teaching model one with sig. value 0.169. IT is less effective than conventional with sig 0.28 ≤ 0.05 or Ho is accepted; CA is more effective than conventional model with sig value 0.723 ≥ 0.05.